2013
DOI: 10.3892/ijo.2013.2181
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis inhibitor therapies for advanced renal cell carcinoma: Toxicity and treatment patterns in clinical practice from a global medical chart review

Abstract: The aim of this study was to assess the treatment patterns and safety of sunitinib, sorafenib and bevacizumab in real-world clinical settings in US, Europe and Asia. Medical records were abstracted at 18 community oncology clinics in the US and at 21 tertiary oncology centers in US, Europe and Asia for 883 patients ≥18 years who had histologically/cytologically confirmed diagnosis of advanced RCC and received sunitinib (n=631), sorafenib (n=207) or bevacizumab (n=45) as first-line treatment. No prior treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 22 publications
2
24
1
Order By: Relevance
“…36 Factors influencing duration of treatment have not been consistently studied. However, retrospective chart review 33,35 and claims database studies 31,32 have shown that a high proportion (15%-40%) of patients will discontinue, reduce dosage, or switch oral RCC treatments due to adverse events. Thus, studies of compliance and persistence patterns are vitally important.…”
Section: Persistence and Compliance Among Us Patients Receiving Pazmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Factors influencing duration of treatment have not been consistently studied. However, retrospective chart review 33,35 and claims database studies 31,32 have shown that a high proportion (15%-40%) of patients will discontinue, reduce dosage, or switch oral RCC treatments due to adverse events. Thus, studies of compliance and persistence patterns are vitally important.…”
Section: Persistence and Compliance Among Us Patients Receiving Pazmentioning
confidence: 99%
“…34,35 In the clinical trial that demonstrated pazopanib was noninferior to sunitinib with regard to PFS, the median duration of exposure to the study drugs was 8 months for pazopanib and 8 months for sunitinib. 36 Factors influencing duration of treatment have not been consistently studied.…”
Section: Persistence and Compliance Among Us Patients Receiving Pazmentioning
confidence: 99%
“…[21][22][23][24] A retrospective database study of dosing patterns of first-line sunitinib, dosed once daily on a 4-weeks-on, 2-weeks-off dosing schedule, showed that patients commonly underwent sunitinib dose reductions within the first 3 treatment cycles due to toxicity and discontinued therapy within the first 5 cycles due to progressive disease. 25 Combined, the findings from these studies suggest that a high percentage of patients in routine clinical settings could discontinue treatment with TKIs in < 6 months.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…With more than 10 years of experience with this agent, there is increased understanding of the mechanism-based AEs associated with sunitinib, the most common of which are hypertension, hypothyroidism, hand-foot syndrome, asthenia/fatigue, neutropenia, and thrombocytopenia. These AEs can lead to dose reductions, interruptions, and discontinuations 11 -all of which may negatively impact outcomes in patients with mRCC. However, some, including hypertension, hypothyroidism, hand-foot syndrome, and neutropenia, have been explored as potential biomarkers of the clinical efficacy of sunitinib.…”
Section: Introductionmentioning
confidence: 99%